The application of the RBII bis in the area of parental responsibility by the Spanish courts: critical commentary on the AAP Barcelona of 23 July 2020 - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This paper will analyze some of the disadvantages encountered by the Spanish courts when a parental responsibility dispute with cross-border elements is brought before them, for the solution of which the solutions established by the RBII bis must be applied. To this end, a critical commentary will be made on the AAP Barcelona of 23 July 2020, in which questions of international jurisdiction are raised, international lis pendens and the effectiveness in Spain of judgments given by the courts of a Member State in relation to the custody, visiting rights and maintenance of a minor.